Model Bisnis Kawasan Strategis Pariwisata Kota Palu Sulawesi Tengah - Firman Syah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
Palu city is the capital city of Central Sulawesi province bordering with Gorontalo Province. Indigenous people who inhabit the city of Palu is a community of Kaili tribe. Palu City was selected as a Special Economic Zone (KEK) for eastern Indonesia and consists of industrial zone, logistics zone and export processing zone. When viewed from the tourism business, there are several famous destinations such as Sibili Lake, Banua Mbaso, Hanging Bridge, Mosque 'Apung' Argam Bab Al Rahman, and Sis Al Jufrie.The method used by writer is qualitative with inductive data analysis. The results found that the city of Palu has shown passion in the field of tourism. Palu City presents a variety of new tourist destinations including natural attractions, culinary tours, and cultural tourism. For example Cars Tusuk Satay, Palu Bay, Four Palu Bridge, Solar Eclipse Monument, Nusantara Pavilion, and Palu Nomori Inscription. Then the tourists need to be given free space to satisfy the needs during a vacation. The business model implemented is that local people can entrepreneurship, gain profit, and create new jobs. Meanwhile, for the government through the Office of Culture and Tourism of Palu City is able to generate Pendapatan Asli Daerah (PAD) in addition to taxes from culinary executed by local communities. To support, the Office of Culture and Tourism of Palu City can hold and coordinate with all the agencies in accordance with their respective work programs. As the development and development of houses to become homestay homes and home industry, the integration of public transportation fleet, and build the concept of Information Management System (SIM) Tourism via online to package the tourism potential of Palu City.